Volcano : The eruption and healing of Mount St. Helens - Lauber, Patricia; Frezzolini, Sylvia (New York : Scholastic, 1986)
An account of how and why Mount St. Helens erupted in May 1980 and the destruction it caused, and a discussion of the return of life to that area.
Keywords: earth science -- non-fiction